Enhancing literacy and numeracy through geometric motifs for batik art in Gayamprit, Klaten - Yuliana, Yuliana; Liadiani, Anifa Mirza; Maulita, Dina; Rahmasari, Luthfi; Muzakiyah, Siti; Sari, Tri Ardilia Maya; Tasari, Tasari; Sholihah, Umi; Anggraheny, Kunthum Ria (Community Empowerment, 2025)
This community engagement project sought to introduce foundational literacy and numeracy skills to children in the Gayamprit area, Klaten, through the creative activity of making Batik with geometric motifs. The program was conducted from March to May 2024. The methodology employed a mixed approach, including trials, hands-on Batik practice, instructional learning, interactive Q&A sessions, reflection, public socialization, and a final exhibition. The initiative successfully cultivated and introduced core literacy and numeracy habits, evidenced by several key outcomes: 100% of participants successfully produced Batik with geometric motifs, demonstrating technical application; 100% of participants were able to correctly and verbally identify the shapes and properties of basic planar geometry, indicating significant numeracy comprehension; all participants actively engaged in the learning process utilizing the Batik media and instructional materials; and the project’s impact was successfully socialized through the final public exhibition. This hands-on, culturally relevant approach proved effective in tangibly enhancing fundamental academic skills among Gayamprit’s children.